2021
DOI: 10.1038/s41598-020-79421-9
|View full text |Cite
|
Sign up to set email alerts
|

Bromelain reduced pro-inflammatory mediators as a common pathway that mediate antinociceptive and anti-anxiety effects in sciatic nerve ligated Wistar rats

Abstract: The involvement of pro-inflammatory mediators complicates the complex mechanism in neuropathic pain (NP). This study investigated the roles of bromelain against pro-inflammatory mediators as a mechanism that underpins its antinociceptive and anti-anxiety effects in the peripheral model of NP. Sixty-four male Wistar rats randomly divided into eight groups, were used for the study. A chronic constriction injury model of peripheral neuropathy was used to induce NP. Tail-immersion and von Frey filaments tests were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…It is interesting to note that suppression of IL1-β might be responsible for the reduction in the level of PGE 2 observed. Our findings showed that IL1-β expression can result to the activation of proinflammatory molecules such as IL-6, SP, PGE 2 through complex signalling cascades [44][45][46] . Evidence has shown that IL1-β just like NGF can modulate excitability of neurons via TRPV1, GABA receptors, sodium channels and NMDA receptors 34 .…”
Section: Discussionmentioning
confidence: 65%
“…It is interesting to note that suppression of IL1-β might be responsible for the reduction in the level of PGE 2 observed. Our findings showed that IL1-β expression can result to the activation of proinflammatory molecules such as IL-6, SP, PGE 2 through complex signalling cascades [44][45][46] . Evidence has shown that IL1-β just like NGF can modulate excitability of neurons via TRPV1, GABA receptors, sodium channels and NMDA receptors 34 .…”
Section: Discussionmentioning
confidence: 65%
“…It is interesting to note that suppression of IL1-β might be responsible for the reduction in the level of PGE 2 observed. Our ndings showed that IL1-β expression can result to the activation of proin ammatory molecules such as IL-6, SP, PGE 2 through complex signalling cascades [53,54,55]. Evidence has shown that IL1-β just like NGF can modulate excitability of neurons via TRPV1, GABA receptors, sodium channels and NMDA receptors [43].…”
Section: Discussionmentioning
confidence: 65%
“… 69 Accumulative experimental evidence has demonstrated that the overproduction of these inflammatory cytokines is necessary and even sufficient to induce chronic pain, memory decline and mood depression in rodents. 7 , 8 , 70 , 71 It has been proposed that the estrogen decline-induced neuronal disorders are mediated by inflammation. 14 While how estrogen decline causes inflammation in nervous system remains unclear.…”
Section: Discussionmentioning
confidence: 99%